A qualitative study of leader behaviors perceived to enable salesperson performance. Issue 4 (2nd October 2019) - Peesker, Karen M.; Ryals, Lynette J.; Rich, Gregory A.; Boehnke, Susan E.
Abstract: This study builds on and extends previous sales leadership research by exploring sales professionals' perceptions of effective leadership behaviors. Semistructured interviews with both sales leaders and salespeople working in a global enterprise software company were examined through a qualitative analysis. Results indicated that participants believed sales leadership played an important role in influencing sales performance. When asked to describe specific sales leader behaviors that best enable salesperson performance, sales professionals – both sales leaders and salespeople – overwhelmingly referenced coaching, followed by collaborating, championing, and customer engaging. We define and describe these four key sales leader behaviors and identify four potential mediating variables (trust, confidence, optimism, and resilience), from which emerges a conceptual framework of sales leader behaviors perceived to enable salesperson performance. We examine these four key sales leader behaviors and mediators in the broader context of leadership theory, particularly transformational, servant, authentic, and adaptive leadership theories. The key contribution of this study is the identification of a set of leader behaviors that are likely to be especially effective in modern sales organizations given that they originated from the perceptions of sales professionals themselves.